Wolność wypowiedzi i prawo do prywatności w społeczeństwie informacyjnym – wybrane aktualne refleksje - Demczuk, Agnieszka (Polityka i Społeczeństwo, 2021)
The measure of civilizational progress is not only economic development, which for several years has been determined by the development of computer science, but also an increase in the level of respect for human rights and freedoms guaranteed in various international legal documents. The Internet is increasingly determining the use of personal, political, social, and economic rights. Public authorities, as part of positive obligations, should be more actively involved in the protection of human rights, especially the freedom of expression and the right to privacy, which are currently being violated quite widely and especially in the horizontal dimension in cyberspace.